Investigating Flexural Strength of Translucent Zirconia Restorations Made by Two Sintering Systems - Almuwash, Jarrah. (Tufts University. Tisch Library., 2019)
ABSTRACT Aim of the study: The aim of this study was to compare the effects of speed sintering on the flexural strength of 5 mol% yttrium partially stabilized tetragonal zirconia polycrystalline (Y-TZP) restorations made in Mihm-Vogt Dental Geratebau GmbH & Co. KG (conventional) and SpeedFire (Speed) sintering ovens. Materials & Methods: Three-unit zirconia fixed partial dentures (FPDs: n = 20) were made from a digital impression and were divided randomly into two groups (10 per group). The first was the long cycle sintering group (LC), which had sintered in the conventional sintering oven with 120 min holding time. The second was the short cycle sintering group (SC), which was sintered in the speed sintering oven, with 35 min holding time. For both ovens company's instructions and recommendations were followed. After sintering, each FPD was placed on a printed metal die, then flexural strength was measured using a universal testing machine and the values were recorded. The two groups were compared using the Mann-Whitney U test, with the level of significance set at 0.05. Results: The LC group demonstrated a lower mean flexural strength, 348.03 ± 47.27 MPa, compared to the SC group, 504.76 ± 211.44 MPa. The Mann-Whitney U test revealed a statistically significant difference between the two groups (p = 0.04), in which the FPDs sintered by SpeedFire exhibited higher flexural strength than the ones sintered in Mihm-Vogt Dental Geratebau GmbH & Co. KG. Conclusions: Within the limitations of this study, it can be concluded that 3-unit zirconia FPDs sintered with the short sintering protocol performed superiorly in terms of flexural strength when compared to those sintered with long sintering protocol.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Posthodontics.; Advisor: Ala Ali.; Committee: Matthew Finkelman, Yukio Kudara, Vasiliki Taskalelli, and Aikaterina Kostaqianni.; Keywords: Dentistry, and Materials Science.